Predicting Trace Metal Exposure in Aquatic Ecosystems: Evaluating DGT as a Biomonitoring Tool - Eismann, Carlos Eduardo [UNESP]; Menegário, Amauri Antonio [UNESP]; Gemeiner, Hendryk [UNESP]; Williams, Paul Nicholas (Springer Nature, 2018)
Exposure to trace metals is a leading factor associated with the development of non-communicable diseases. Aquatic ecosystems are not only effective agents of trace metal dispersion but are also at risk of contaminant enrichment. The use of sentinel organism as indicators of water quality is one method to evaluate potential human and ecological risk. An alternative or companion approach is to employ chemical techniques that mimic biotic accumulation/responses by aquatic fauna. The Diffusive Gradients-in-Thin-Films (DGT) technique has been widely used in bioavailability studies in water, soil and sediment. Many efforts have been made trying to understand the relationships between DGT labile determinations of trace elements and its biouptake by different organisms. However, the relationship between DGT labile determinations and the biological accumulation/response in aquatic animals is still not clear. The present work aims to improve the understanding of this relationship by summarizing the works using DGT devices and accumulation/response by animals in aquatic media. Several papers studying nineteen different elements in aquatic media are revised and discussed. The papers were separated and discussed in four categories: DGT and Biotic response, DGT and Bioaccumulation, DGT and Biomonitoring, and DGT and Bioturbation. DGT is expected to correlate well with the biological accumulation/responses in kinetically controlled situations. In biomonitoring studies, the use of chemical (DGT) and biological approaches gives complementary and high valuable information. The use of DGT and biological approaches should be considered in future studies about bioavailability and might improve the comprehension about uptake of trace metals by the aquatic fauna.
Keywords: Aquatic media; Bioavailability; DGT labile species; Exposure analysis; Global water pollution